Contemplating Resectability - Shuman, Andrew G. (The Hastings Center report, 2017)
Suzie loves to talk. A successful mid-thirties businesswoman, she is a self-described social butterfly—which made her diagnosis of tongue cancer even more devastating. She came to the clinic complaining of a lump in her throat, which in most young healthy people turns out to be benign and easily treated. But not for Suzie, who had a very rare salivary tumor arising in the back of her tongue. Its slow growth was both a blessing and a curse; such tumors do not kill people quickly, but they typically require surgery. It would slowly and relentlessly grow until and unless we removed most of her tongue. In head and neck surgery, issues of appearance, identity, function, and communication are the foremost considerations when we decide when, and whether, to operate. As the adage goes, knowing when not to operate is the sine qua non of the wise surgeon. But the inverse is also true.